Ethnic Diversity and Civil War - Thomas P. Tangerås; Nils-Petter Lagerlöf (The Research Institute of Industrial Economics (IUI), 2002)
We construct a model in which a number of equally powerful ethnic groups compete for power by engaging in civil war. In non-redistributive equilibrium, ethnically homogeneous and ethnically diverse countries face a lower probability of civil war than countries with a moderate degree of ethnic diversity. The likelihood of conflict is maximized when there are two ethnic groups. When rent-extraction possibilities are not too big and society sufficiently ethnically homogeneous, there also exists a pacific equilibrium path sustained by redistribution from the ruling group to the out-of-power groups.
Keywords: H56; J15; K42; N40; N47; 330; Civil War; Ethnic Diversity; Redistribution; Dynamic Game; Bürgerkrieg; Dynamisches Spiel; Ethnische Beziehungen